2016
DOI: 10.1186/s12933-016-0426-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum gamma-glutamyltransferase is not associated with subclinical atherosclerosis in patients with type 2 diabetes

Abstract: BackgroundThis study investigated the association between serum gamma-glutamyltransferase (GGT) level and subclinical atherosclerosis in patients with type 2 diabetes.MethodsThis cross-sectional study involved 1024 patients with type 2 diabetes mellitus. Measurement of brachial-ankle pulse wave velocity (baPWV; as a marker of arterial stiffness) and an ultrasound assessment of carotid atherosclerosis were performed. Subclinical atherosclerosis was defined by the presence of a high baPWV (≥1720 cm/s), carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In this study, serum lipid or GGT levels were lower in the DCVD patient group than in the control group. Previous studies have reported that elevated GGT and CRP levels increased the risks of dyslipidemia, metabolic syndrome, and CVD, yet their prognostic values of CVD events in T2D patients remain controversial [ 15 , 16 ]. As reported in a general population-based cohort study, increased CVD risk due to low education and wealth levels has also been observed in Korean T2D patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, serum lipid or GGT levels were lower in the DCVD patient group than in the control group. Previous studies have reported that elevated GGT and CRP levels increased the risks of dyslipidemia, metabolic syndrome, and CVD, yet their prognostic values of CVD events in T2D patients remain controversial [ 15 , 16 ]. As reported in a general population-based cohort study, increased CVD risk due to low education and wealth levels has also been observed in Korean T2D patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the number of SNPs included in the model increased, the mean difference (MD) in liability to DCVD between cases and controls increased (MDs: 0.006, 0.044, and 0.216 for GLT 15 , GLT 47 , and GLT 231 , respectively). For every 1-point increase in normalized genetic liability on a scale of 0 to 10, the risk of developing DCVD also increased accordingly (ORs: 1.05, 1.54, and 14.13 for GLT 15 , GLT 47 , and GLT 231 , respectively) (Table 4).…”
Section: Dcvd Risk Prediction 241 Genetic Risk Predictionmentioning
confidence: 99%
“…In recent years, accumulated evidences have demonstrated that serum elevated GGT level is associated with cardiovascular diseases, metabolic syndrome, diabetes mellitus, cancer, chronic kidney disease, fractures, cardiovascular mortality and all-cause mortality [9,[19][20][21][22][23][24]. GGT as a key transferase enzyme plays a vital role in the resynthesis of glutathione (GSH), which is an important intracellular antioxidant protecting cells against oxidative damage [22,25]. GGT levels may elevate in order to produce more GSH in response to oxidative stress [26].…”
Section: Discussionmentioning
confidence: 99%
“…γ-glutamyltransferase (GGT), as a kind of membranebinding enzyme, is critical to the regeneration of intracellular glutathione, a major cellular antioxidant (3,4). Serum GGT is a well-known marker of liver diseases and alcohol abuse (5).…”
Section: Introductionmentioning
confidence: 99%